H2S biofiltration using expanded schist as packing material: influence of packed bed configurations at constant EBRT. Issue 1 (27th June 2014) - Courtois, Amaury; Andrès, Yves; Dumont, Éric
Abstract BACKGROUND H2S biofiltration was carried out using expanded schist as packing material completed with a synthetic material (UP20). A comparison of different hydrodynamic configurations was made based on biofilter performances and pressure drop measurements. Three biofilters (namely BF52, BF102 and BF160) differing in bed height (52 cm, 102 cm and 160 cm, respectively) and diameter (14 cm, 10 cm and 8 cm, respectively) were designed in order to contain the same volume of expanded schist (8 L). RESULTS Biofilters were operated for more than 6 months at a constant flow rate (1.5 Nm3 h−1 corresponding to an empty bed residence time of 19 s). Elimination capacities and removal efficiencies were calculated according to loading rates varying from 0 to 57 g m−3 h−1 (inlet concentration up to 300 mg m−3). Biofilter performances were modeled and biokinetic constants were calculated using the Ottengraf model and a modified Michaelis–Menten model. In terms of elimination capacity, biofilter configurations can be ordered from the most to the least efficient: BF160 > BF102 > BF52 (maximum removal rates of 36.4, 30.3 and 25.1 g m−3 h−1, respectively). CONCLUSION From the Ottengraf model, it was calculated that the specific surface area covered with biofilm, relative to BF52, was 21% and 45% higher for BF102 and BF160, respectively. © 2014 Society of Chemical Industry